The Ethical Implications of AI-Driven Digital Marketing Development : A Qualitative Study in the Indonesian Business Landscape - Mohamad Chaidir; Ruslaini Ruslaini; Seger Santoso (Universitas Kristen Indonesia Toraja, 2022)
This study investigates the ethical implications of AI-driven digital marketing development within the Indonesian business landscape. The research aims to explore the ethical considerations surrounding the integration of artificial intelligence in digital marketing practices and its impact on businesses operating in Indonesia. Employing a qualitative approach, the study utilizes in-depth interviews with key stakeholders in the digital marketing industry, including marketers, consumers, and industry experts. A purposive sampling technique is employed to select participants with diverse perspectives and experiences related to AI-driven digital marketing. Data analysis involves thematic analysis to identify emerging themes and patterns regarding ethical dilemmas, concerns, and best practices in AI-driven digital marketing. The findings highlight the complex ethical challenges faced by businesses in leveraging AI technology for marketing purposes in Indonesia and provide insights into potential strategies for addressing these challenges responsibly.